Natural Products in Diabetes Research: Quantitative Literature Analysis - Echeverria-Morgado, J (Taylor and Francis Ltd., 2021)
The current study aimed to identify which natural products and which research directions are related to the major contributors to academic journals for diabetes therapy. Bibliometric data were extracted from the Web of Science online database using the search string TOPIC = (‘‘natural product*’ OR ‘‘natural compound*’ OR ‘‘natural molecule*’ OR ‘phytochemical*’ OR ‘‘secondary metabolite*’) AND TS = (‘diabet*’) and analysed by a bibliometric software, VOSviewer. The search yielded 3694 publications, which were collectively cited 80,791 times, with an H-index of 117 and 21.9 citations per publication on average. The top-contributing countries were India, the USA, China, South Korea and Brazil. Curcumin, flavanone, resveratrol, carotenoid, polyphenols, flavonol, flavone and berberine were the most frequently cited natural products or compound classes. Our results provide a brief overview of the major directions of natural product research in diabetes up to now and hint on promising avenues for future research. © 2020 Informa UK Limited, trading as Taylor & Francis Group.